Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Makanan dan minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014 - Bayu Dewantara, Rahadyan, Ahmad Mardalis, SE.,MBA (2015)
The purpose of this research is to know and measure the influcences between profitability, firm size, and liquidity to capital structure of foods and beverages company which listed in Indonesia Stock Exchange in 2010-2014 period. Data used in this research is secondary data which is financial statements collected from Indonesia Capital Market Directory (ICMD) and also from www.idx.co.id. For determining samples using purposive sampling method that is determining sample by creating some criteria. From that method there are 14 company that match with certain criteria. The amount of data of this research obtained by using pooling data method that is multiplying the the amount of the company which are 14 company, and the period which are 5 years so tha data are 70. Data analysis using linear regression method. Hypothesis test using t test to know the individual influence between independent variables to dependent variabel. F test used to know the simultaneous influences between profitability, firm size, and liquidity to capital structure. coefficient regression also used to know the ability of independent variables on determining the dependent variable. The result of this research shows that capital structure is simultaneously influenced by profitability, firm size, and liquidity. Only liquidity has the significantly negative influence to capital structure. On the other side, profitability and firm size indiviudaly have no significant influence to capital structure. from the coefficient regression test known that 29,3% of dependent variable can be explained by independent variables.